Effect of temperature on equilibria in synthetic sulfuric acid leaching solution of zinc calcine - Lee, MS; Lee, KJ; Oh, YJ (JAPAN INST METALS, 2004)
In order to simulate the leaching of zinc calcine by sulfuric acid solutions, we prepared synthetic solutions with the composition ZnSO4-Fe-2(SO4)(3)-NaZSO(4)-H2SO4-NaOH-H2O and measured the solution pH at various temperatures. The effect of temperature on the ionic equilibria of these solutions was analyzed by considering chemical equilibria, mass balance and charge balance equations. The activity coefficients of solutes and the activity of water were calculated by using the Pitzer equation. The mole fractions of iron species were greatly affected by the solution temperature and the concentration of Fe-2(SO4)(3). In the experimental ranges of ionic strength of solution up to 9 m, the pH values calculated in this study agreed well with those measured.
Keywords: AQUEOUS-SOLUTIONS; ELECTROLYTES; SYSTEMS